Information studies and science in Vytautas Didysis university - Kaminskas, ytautas (Information & Media, 1994)
General information studies in the University consists of two levels: informatics for the beginners and computers application. Students can freely choose between them. The article describes the special education in informatics. The main subjects of these studies are shortly described.